Phosphorylation of p65(RelA) on Ser547 by ATM Represses NF-κB-Dependent Transcription of Specific Genes after Genotoxic Stress - Sabatel, Hélène; Di Valentin, Emmanuel; Gloire, Geoffrey; Dequiedt, Franck; Piette, Jacques; Habraken, Yvette (PLOS ONE, 2012)
The NF-κB pathway is involved in immune and inflammation responses, proliferation, differentiation and cell death or survival. It is activated by many external stimuli including genotoxic stress. DNA double-strand breaks activate NF-κB in an ATM-dependent manner. In this manuscript, a direct interaction between p65(RelA) and the N-terminal extremity of ATM is reported. We also report that only one of the five potential ATM-(S/T)Q target sites present in p65, namely Ser547, is specifically phosphorylated by ATM in vitro. A comparative transcriptomic analysis performed in HEK-293 cells expressing either wild-type HA-p65 or a non-phosphorylatable mutant HA-p65S547A identified several differentially transcribed genes after an etoposide treatment (e.g. IL8, A20, SELE). The transcription of these genes is increased in cells expressing the mutant. Substitution of Ser547 to alanine does not affect p65 binding abilities on the κB site of the IL8 promoter but reduces p65 interaction with HDAC1. Cells expressing p65S547A have a higher level of histone H3 acetylated on Lys9 at the IL8 promoter, which is in agreement with the higher gene induction observed. These results indicate that ATM regulates a sub-set of NF-κB dependent genes after a genotoxic stress by direct phosphorylation of p65.